TULAK PALONG TRADITION IN LAYEUN COMMUNITY, ACEH BESAR: TRADISI TULAK PALONG DALAM MASYARAKAT LAYEUN, ACEH BESAR - Natasya, Andra; Ismail, Sanusi; Abubakar, Bustami (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2023)
This study aims to examine the symbolic meaning of the tulak palong tradition among the people of Layeun-Aceh Besar. Palong is a type of traditional boat used by fishermen on the coast of Aceh Besar. This study uses a qualitative approach in which data is collected through observation, interviews, and documentation. The informants in this study were panglima laot, fishermen, and the local community. The results of the study show that the tulak palong tradition has been practiced in this area since 1970. The tulak (refusal) process is only carried out the first time when the palong is about to sail, and then the palong will continue to be at sea until it needs to be renovated, usually in 2 to 5 years. In the implementation of tulak palong, there are social values, including mutual cooperation and caring for others. In addition to social values, in the process of practicing tulak palong, there are also symbolic meanings such as beauty in decorating the palong, brotherhood among the community.